Are Black Children Disproportionately Overrepresented in Special Education? A Best-Evidence Synthesis. (January 2017) - Morgan, Paul L.; Farkas, George; Cook, Michael; Strassfeld, Natasha M.; Hillemeier, Marianne M.; Pun, Wik Hung; Schussler, Deborah L.
We synthesized empirical work to evaluate whether Black children are disproportionately overrepresented in special education. We identified 22 studies that met a priori inclusion criteria including use of at least 1 covariate in the reported analyses. Evidence of overrepresentation declined markedly as the studies included one or more of 3 "best-evidence" methodological features (i.e., analyses of individual-level data, a nationally representative sample, a control for individual-level academic achievement). Among 48 coefficient estimates from studies with the strongest internal and external validity, only 1 (2.1%) indicated significant overrepresentation. This coefficient suggested a school characteristic (a high percentage of minority students) that may help explain underrepresentation. None of the remaining 47 (97.9%) regression coefficients indicated that Black children's overrepresentation in special education was explained by misidentification based on race or ethnicity. Instead, the best evidence indicates that Black children are significantly less likely than otherwise similar White children to receive special education services.